The Complex Intersection: Barriers to Gender Affirmation Surgery and Mental Health in Pakistan's Transgender Community - Sana Abbas; Usman Saqib (Majalah Kesehatan Indonesia, 2026)
This study aims to investigate the structural barriers to accessing gender affirmation surgery (GAS) and evaluate the resulting impact on the mental health of transgender individuals in Pakistan. Conducted through a cross-sectional survey from January to March 2025, the study engaged 500 transgender individuals across five major Pakistani cities: Karachi, Lahore, Islamabad, Peshawar, and Quetta. Data were gathered via a structured questionnaire encompassing demographics, healthcare barriers, and mental health metrics. Mental health indicators, including depression (42%), anxiety (38%), and PTSD (21%), were documented based on participant self-report of formal clinical diagnoses received prior to the study. The results reveal a stark reality: only 9% (n=45) of respondents had successfully undergone full GAS, while a substantial majority (61%, n=305) expressed a strong desire for the procedure but faced insurmountable obstacles. The most prominent barriers identified were the prohibitive high cost (73%) and a critical lack of specialized surgeons (56%). A mental health crisis is evident, with 74% of participants reporting regular symptoms of distress. A statistically significant association was established between the desire for surgery and heightened mental distress (x2 = 17.94, df = 1, p < 0.001), with a Cramer’s V of 0.19, indicating a moderate effect size. This research highlights a systemic failure at the intersection of healthcare, socio-legal policy, and mental health support, calling for urgent reforms such as financial subsidies and the integration of transgender health into medical education.